Increase in nitrogen, phosphorus, and potassium of liquid fertilizer from fish canning waste and kepok banana peel (Musa paradisiaca L.) - Rieny Sulistijowati; Dwi Angriani Habie; Wila Rumina Nento; Elanemay Ivonne Peleh (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Canned fish industry production generates significant waste, which, if left untreated, can pollute the environment and have negative impacts. While solid waste from fisheries has been widely utilized, the utilization of liquid waste from fisheries remains uncommon. This research aims to analyze the chemical quality of liquid organic fertilizers and determine the best treatment between liquid waste from pelagic tuna canning and kepok banana peel extract. The research employed a laboratory experimental method with one treatment, which is different concentrations of liquid waste from fish canning and kepok banana peel extract, with four treatment levels and three replications: PO (700 mL liquid waste from fish canning), P1 (600 mL liquid waste from fish canning + 100 mL kepok banana peel extract), P2 (550 mL liquid waste from fish canning + 150 mL kepok banana peel extract), and P3 (500 mL liquid waste from fish canning + 200 mL kepok banana peel extract). The parameters observed were nitrogen (N) content, phosphorus (P) content, and potassium (K) content. The research data were analyzed using a completely randomized design (CRD). The data analysis results stated that the treatment levels of P0, P1, P2, and P3 had a significant effect on the quality of liquid organic fertilizer and were statistically significantly different on the levels of nitrogen, phosphorus, and potassium of liquid organic fertilizer products. The results indicate the appropriate formulation for liquid organic fertilizers nd the best chemical quality, which is treatment level P2 with a formulation of 550 mL. liquid waste from fish canning, 150 mL. kepok banana peel extract, 300 mL. coconut water, and 40 mL EM4, yielding nitrogen (N), phosphorus (P), and potassium (K) values of 3.18%, 5.47%, and 5.54%, respectively. These values meet the quality standard requirements for liquid organic fertilizers according to Minister of Agriculture Regulation number 70/Permentan/SR.140/10/2011, which is between 3-6%.Keywords:Fish wasteLiquid organic fertilizerNitrogenPhosphorusPotassium